Factors related to sustainable employment of people with acquired brain injury or spinal cord injury: The employer's perspective - Barbara Schiffmann; Monika E. Finger; Katarzyna Karcz; Katarzyna Karcz; Stefan Staubli; Bruno Trezzini (Frontiers Media S.A., 2022)
BackgroundOf those people with an acquired brain injury (ABI) or spinal cord injury (SCI) who initially successfully returned to paid employment, some exit the workforce before reaching official retirement age. Employers play a central role in ensuring a sustainable work situation for employees with a disability and in preventing such exits. However, the factors and mechanisms involved from the employer's perspective are still poorly understood.PurposeThe purpose was to determine factors which, from employer's perspective, have a particularly positive or negative influence on sustainable employment of people with ABI or SCI.MethodsTwenty semi-structured interviews were conducted with employers of people with ABI or SCI and thematically analyzed.ResultsIdentified factors could be assigned to four thematic areas for both health conditions: socio-demographic and psychological characteristics of the disabled person, their work performance, the work environment, and other social/environmental conditions. Good disability self-management and proactive communication of needs on the part of the employee are contributing factors to long-term employment from the employer's perspective. Differing expectations and assessments of work performance by employees and employers pose a challenge. Employers feel a responsibility to provide an optimal work environment to allow the employee with a disability to reach his or her full potential. This includes appropriate work tasks, development opportunities, a compassionate work team, flexible work arrangements, providing resources to address specific needs, and an inclusive culture. Employers find the support provided by occupational specialists very helpful, as they often lack the knowledge to design the work environment to meet the person's needs.ConclusionsEmployers emphasize the benefits of professional support during vocational rehabilitation to prepare employers and employees for long-term, sustainable employment. Such support is often lacking when changes and problems occur at a later stage. Therefore, people with a disability should be able to communicate their work-related needs and take charge of their own health so that problems that arise can be addressed as early as possible. Continued awareness of the environment is also beneficial. In addition, the expansion of low-threshold health-specific support services for long-term problems was found to be of great importance for employers in Switzerland.